2020
DOI: 10.1021/acschemneuro.0c00019
|View full text |Cite
|
Sign up to set email alerts
|

Underpinning the Neurobiological Intricacies Associated with Opioid Tolerance

Abstract: The opioid crisis is a major threat of the 21st century, with a remarkable juxtaposition of use and abuse. Opioids are the most potent and efficacious class of analgesics, but despite their proven therapeutic efficacy, they have recently been degraded to third-line therapy for the management of chronic pain in clinics. The reason behind this is the development of potential side effects and tolerance after repeated dosing. Opioid tolerance is the major limiting factor leading to the withdrawal of treatment, sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…Although it has been widely established that opioid drugs are critical to proper pain management and that their receptor desensitisation is closely associated with opioid tolerance, the role of inflammation and the associated molecular mechanisms in this phenomenon have not been well studied until relatively recently ( 13 ). A growing body of literature suggests that activated microglia and astrocytes (glia) are the primary targets in pain management, because of their function in pain transmission and opioid analgesia ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been widely established that opioid drugs are critical to proper pain management and that their receptor desensitisation is closely associated with opioid tolerance, the role of inflammation and the associated molecular mechanisms in this phenomenon have not been well studied until relatively recently ( 13 ). A growing body of literature suggests that activated microglia and astrocytes (glia) are the primary targets in pain management, because of their function in pain transmission and opioid analgesia ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Opioids are frequently used for moderate to severe pain state, but they are associated with several toxic side effects which include respiratory depression, nausea and vomiting, constipation, sedation, and cognitive deficits . Eventually, addiction and tolerance that develop with prolonged opioid use led to the fall of opioids from the first line to the second and third line treatment options . It was also observed that opioid use is increasing the likelihood of bone destruction and tumor growth in BCP condition, giving all the more reason to avoid treatment with opioids .…”
Section: Current Therapeutic Strategies and The Potential Bottlenecks...mentioning
confidence: 99%
“…For examination of peripheral analgesia, studies have shed light on the peripheral analgesic tolerance [68,69]. Research on the development of the centrally mediated opioid analgesic tolerance and related mechanisms has been reviewed extensively elsewhere [20,23,[70][71][72]. Available evidence related to peripheral analgesia and analgesic tolerance is summarized below.…”
Section: Contribution Of Peripheral Mors To Opioid-induced Analgesia and Analgesic Tolerancementioning
confidence: 99%